2006
DOI: 10.1001/archpsyc.63.6.639
|View full text |Cite
|
Sign up to set email alerts
|

Differential and Brain Region–Specific Regulation of Rap-1 and Epac in Depressed Suicide Victims

Abstract: Given the importance of Rap-1 in neuroprotection and synaptic plasticity, our findings of differential regulation of Rap-1 and Epac between brain regions suggest the relevance of these molecules in the pathophysiology of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 64 publications
3
36
0
Order By: Relevance
“…In addition, it is likely that compounds to modulate the levels of expression and function of the KLF11-MAO-mediated pathway may increase neuroprotection, neuroplasticity, and synaptic activities. Maximizing the therapeutic effects upon these targets is also essential toward achieving comprehensive management of stress-induced, frequently treatmentresistant, psychiatric illnesses, and addictions (Barr et al, 2004;Beasley et al, 2005;Dwivedi et al, 2006;Frazer, 1997;Mitchell et al, 2012;Sanacora, 2008;Sawada et al, 2005;Silberman et al, 2009;Wallace et al, 2007). Thus, the new knowledge generated by the current study has mechanistic relevance and also provides the rationale for targeting this pathway to develop potential novel therapeutics approaches in the treatment of MDD.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it is likely that compounds to modulate the levels of expression and function of the KLF11-MAO-mediated pathway may increase neuroprotection, neuroplasticity, and synaptic activities. Maximizing the therapeutic effects upon these targets is also essential toward achieving comprehensive management of stress-induced, frequently treatmentresistant, psychiatric illnesses, and addictions (Barr et al, 2004;Beasley et al, 2005;Dwivedi et al, 2006;Frazer, 1997;Mitchell et al, 2012;Sanacora, 2008;Sawada et al, 2005;Silberman et al, 2009;Wallace et al, 2007). Thus, the new knowledge generated by the current study has mechanistic relevance and also provides the rationale for targeting this pathway to develop potential novel therapeutics approaches in the treatment of MDD.…”
Section: Discussionmentioning
confidence: 97%
“…The MAO A-repressor, R1, in depressive disorder S Johnson et al MAO A synthesis associated with current treatment resistance; (2) prevent the recurrence of depressive episodes because commonly prescribed drugs (such as SSRIs) neither inhibit MAO A levels nor specifically target R1 (Meyer et al, 2009); (3) reduce MAO A-mediated apoptotic cell death, increase neuroprotection, and promote neuroplasticity; maximizing these effects is also relevant to the treatment of depressive disorders (Dwivedi et al, 2006;Sanacora, 2008). Subsequent studies should also address the application of R1 levels as a potential diagnostic marker for depressive disorders and treatment assessment by measuring blood levels of this protein in current and future patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both Epac1 and Epac2 are expressed in the retina [19]. It has been shown that Epacs have a profound role in cognition, loss of Epacs leads to impairment in memory retrieval in a fear conditioning paradigm [34], and it is also noted that in depressed patients, the Epac2 expression but not Epac1 is altered in the cortex [35]. Besides, Epac2 participates in synaptic plasticity [17,36].…”
Section: Epac2mentioning
confidence: 99%